2016
DOI: 10.1007/s11251-016-9368-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of comparing contrasting cases and inventing on learning from subsequent instructional explanations

Abstract: Comparing contrasting cases is a promising means to prepare learners for future learning from related direct instruction. The most prevalent type of preparation intervention used in this case comparison approach is providing contrasting cases together with comparison prompts. However, if the contrasting cases are complex learners might need more guidance than mere prompts in order to detect their relevant similarities and differences and thus exploit their full potential. The inventing approach entails having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…Second, the intervention was implemented by classroom teachers and integrated in authentic curriculum‐based tasks that mattered for the students in terms of academic performance, which likely increased their will to engage in sourcing activities (Paul, Macedo‐Rouet, Rouet, & Stadtler, ). Third, the detailed case descriptions and the strong focus on the distinguishing features of adaptive sourcing that characterized the contrasting cases approach gave the intervention students rich opportunities to learn the principles of adaptive sourcing required for transfer (Nagarajan & Hmelo‐Silver, ; Roelle & Berthold, , ; Sidney et al., ). Finally, the intervention lasted longer than most other sourcing interventions implemented to date (Brante & Strømsø, ; Bråten, Stadtler, & Salmerón, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the intervention was implemented by classroom teachers and integrated in authentic curriculum‐based tasks that mattered for the students in terms of academic performance, which likely increased their will to engage in sourcing activities (Paul, Macedo‐Rouet, Rouet, & Stadtler, ). Third, the detailed case descriptions and the strong focus on the distinguishing features of adaptive sourcing that characterized the contrasting cases approach gave the intervention students rich opportunities to learn the principles of adaptive sourcing required for transfer (Nagarajan & Hmelo‐Silver, ; Roelle & Berthold, , ; Sidney et al., ). Finally, the intervention lasted longer than most other sourcing interventions implemented to date (Brante & Strømsø, ; Bråten, Stadtler, & Salmerón, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Roelle and Berthold (, ) showed that, at least when the contrasting cases are complex, learners may profit from high amounts of instructional guidance and, conversely, that contrasting cases may be less beneficial when learners are only prompted to compare the cases. In these studies, high guidance conditions involved students being provided with model answers to the comparison prompts, which highlighted the dimensions in which the two cases differed.…”
Section: Learning Through Contrasting Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine fachdidaktische Strukturierungshilfe zurK onzeptanwendung bietend ie Basiskonzepted er Chemie [14].I mF okus unsererL erngelegenheitsteht diesbezüglichdie Frage, welchenEinflussSubstituentenals Strukturmerkmalauf dieEnergie unddarausresultierenda uf dieG eschwindigkeit einerR eaktionh aben, die weiterhind em gleichen Reaktionspfadf olgt undw ie dieser Einfluss fachgerechtbegründet werden kann. Diesem zuträgliche rscheintinsbesondere beikomplexen,nur konzeptbasiert zu erklärenden Inhalten einh ohes Maßa nI nstruktion unde ine Mçglichkeitz ur Prüfung entwickelter Erklärungen [18].I n derC hemiedidaktikh at dieser Ansatz bisher nurv ereinzelt Anwendungg efunden. Mite inem Satz vonC ontrasting Casesw irdd er Fachgegenstands omit in seinen Va riationen systematisch erfasst.…”
Section: Fachdidaktischer Ansatzund Fachwissen-schaftlichesachzusammeunclassified
“…In this paper, we investigate teacher talk guidance in an exploratory task called Invention (Schwartz & Bransford, 1998;Schwartz & Martin, 2004), during which students attempt to invent representations to describe a set of data or examples. Research on effective guidance for Invention activities has yielded conflicting results (Chase, Connolly, Lamnina, & Aleven, 2019;Holmes, Day, Park, Bonn, & Roll, 2014;Kapur, 2011;Loibl & Rummel, 2014;Roelle & Berthold, 2016); however, no work has explored teacher talk guidance of Invention.…”
Section: Introductionmentioning
confidence: 99%